How to prepare optimum cell blocks in lung cancer: Opinion - Fanny S Desai (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Fine needle aspiration with cell blocks can diagnose lung cancers in high risk patients. As ancillary study is important for lung cancer diagnosis, subtyping and prediction of targeted therapy response, it is important that cell block made have good cellularity and morphology. Here we describe the novel cell block preparation technique for pulmonary cytology specimens in which sediments from centrifuged aspirates were collected on layered filter papers followed by application of partially melted 2% agarose gel on cell button. Out of 41 cell blocks, 22 cases of lung cancers were subtyped without immunohistochemistry. Immunohistochemistry was done in 14 cases for subtyping. Four cases showed only benign respiratory epithelium with fibrosis. We found adequate cellularity in all cases (100%), however confirmatory diagnosis could not be given in 4 (9.7%) cases.